Cardiovascular ATIP (Angiotensin receptor type 2 interacting protein) expression in mouse development. Issue 5 (22nd January 2014) - Bundschu, Karin; Schuh, Kai
<x xml:space="preserve">Abstract</x> Background: ATIPs (Angiotensin receptor type 2 [AT2] interacting proteins) are described as AT2 interacting protein variants, whereas their expression and functions during development are not known yet. Results: Here, we provide a detailed expression pattern of ATIP variants during mouse development by visualizing Mtus1 promotor activity, Mtus1 RNA, and subsequent ATIP protein expression. ATIPs are strongly expressed in the developing cardiovascular system, including the vascular plexus of the yolk sac and the fetal vascular part of the placenta. Moreover, ATIP is expressed spatially distinct during eye and limb bud development, and in later stages in lung and nervous system. The three murine ATIP isoforms are expressed in a distinct manner, whereupon isoform 1 and 4 are correlated to cardiovascular, lung, and limb bud development and isoform 3 is restricted to brain and eye development. Interestingly, Mtus1 expression is not necessarily correlated to Agtr2 expression, suggesting novel but yet unknown functions for ATIP, independent of AT2 signaling. Conclusions: ATIPs seem to be mainly involved in the developmental regulation of the cardiovascular system and may act in different AT2‐dependent and ‐independent manners. Hence, these results deliver valuable information to further elucidate the different functions of ATIPs in the processes of mammalian development. Developmental Dynamics 243:699–711, 2014. © 2013 Wiley Periodicals, Inc.